Performance study of mobile IPV6 extensions - Haseeb,Shariq (Kulliyyah of Engineering,International Islamic University Malaysia, 2006)
Mobile IP is the Internet Engineering Task Force proposal to cater for All-Internet Protocol based mobility. It forms the backbone for next generation Wireless Internet Technology to provide uninterrupted network service while on the move. Mobility of the nodes requires them to detach themselves from one network and attach to another network in order to receive service. This change from one domain to another requires the old IP connections to be terminated and new connections to be established. Mobile IP describes a solution to this problem and does not require any modifications to the existing routers. This thesis conducts a performance study of the various Mobile IPv6 protocols such as standard Mobile IPv6, Hierarchical Mobile IPv6, Fast handoff Mobile IPv6, their combination and Simultaneous Bindings Mobile IPv6. The thesis benchmarks the protocol variations against the standard Mobile IPv6 protocol, by studying them under Quality of Service parameters. We propose three evaluation models consisting of linear movement of a single node to study the latency in TCP, ping-pong movement of a single node to study the network throttling and robustness analysis by starting with 5 mobile nodes and then gradually (5 nodes per stage) increasing the mobile nodes to 50. The proposed network models are then simulated in an open source simulator ns- 2. Simultaneous Bindings proved to have had the lowest amount of packet loss because it has the ability to maintain more than one simultaneous connection. It also observed that Simultaneous Bindings can be implemented on top of Fast Handoff protocol without much modifications.